2023
DOI: 10.1186/s12964-023-01125-0
|View full text |Cite
|
Sign up to set email alerts
|

What is new in cancer-associated fibroblast biomarkers?

Abstract: The tumor microenvironment is one of the important drivers of tumor development. Cancer-associated fibroblasts (CAFs) are a major component of the tumor stroma and actively participate in tumor development, invasion, metastasis, drug resistance, and other biological behaviors. CAFs are a highly heterogeneous group of cells, a reflection of the diversity of their origin, biomarkers, and functions. The diversity of CAF origin determines the complexity of CAF biomarkers, and CAF subpopulations expressing differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 258 publications
1
11
0
1
Order By: Relevance
“…While not all liver-CAF samples exhibited distinct signatures, it is conceivable that the CAF low samples encompass either less activated fibroblasts or distinct subpopulations. Previous research has identified different CAF-clusters (Yu et al, 2022; Zou et al, 2022) and it was even speculated that CAF subpopulations expressing different biomarkers might either promote or counteract tumor growth (Han et al, 2020; Zhao et al, 2023). In addition, Ma et al have recently delved into the heterogeneity of CAF subsets using single cell gene expression data across different cancer types (Ma et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While not all liver-CAF samples exhibited distinct signatures, it is conceivable that the CAF low samples encompass either less activated fibroblasts or distinct subpopulations. Previous research has identified different CAF-clusters (Yu et al, 2022; Zou et al, 2022) and it was even speculated that CAF subpopulations expressing different biomarkers might either promote or counteract tumor growth (Han et al, 2020; Zhao et al, 2023). In addition, Ma et al have recently delved into the heterogeneity of CAF subsets using single cell gene expression data across different cancer types (Ma et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, analysis of methylome and transcriptome data consistently identified CAF high samples with abnormal expression, particularly in candidate CAF-markers such as RUNX3 (Koyama et al, 2023) and EDARADD (Lawrence et al, 2020). The heterogeneity in CAFs in transcriptome and DNAm might also originate from different cellular sources recruited into the CAF compartment (Zhao et al, 2023). Nevertheless, our analysis suggests that CAF-associated DNAm profiles closely resemble those of normal fibroblasts, hinting at a fibroblastoid cellular origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To what concern genes related to the activation of fibroblast into CAFs, the gene set for CAF signature was composed of COL1A1, COL1A2 [76], VEGF, TGFβ1 [77,78], fibronectin [79,80], IGF1 [81][82][83], and VIM [84,85]. In addition to these genes, CAFs also gain further secretory phenotypes and ECM production/remodeling [84].…”
Section: Gene and Protein Expression Analysis Of 3d Bioprinting Pancr...mentioning
confidence: 99%
“…VIM expression in CAFs from PDAC patients is associated with significantly shorter overall survival [84]. VIM expression in CAFs is related to tumorigenesis, metastasis, recurrence, drug resistance, and poor prognosis in patients with several other cancers [85].…”
Section: Gene and Protein Expression Analysis Of 3d Bioprinting Pancr...mentioning
confidence: 99%